The Effect of Elections on Capital Expenditure and Social Assistance Expenditure - Yenie Eva Damayanti; Ahmad Karim (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2021)
The purpose of this study was to determine the differences in the allocation of capital expenditures and social assistance expenditures before and during the election of regional heads. This study uses the Wilcoxon test as a non-parametric test. The results showed that the proportion of capital expenditure and social assistance expenditure during the election was not greater than the proportion of capital expenditure and social assistance expenditure before the election. However, the proportion of capital expenditure during the election was not different from before the election.